An investigation into athlete identity and contentment with life from the perspective of sports high school students - Omer Faruk Yazici; Mustafa Baris Somoglu (ROL Spor Bilimleri Dergisi, 2023)
This study aims to determine athlete identities and life satisfaction levels of students in sports high schools in Turkey, to reveal the relationships between and to examine them based on certain variables. The sample consists of a total of 2734 students, of which 2008 (73.4%) male and 726 (26.6%) female, continuing their education and training activities in sports high schools in 2020-2021 academic year in Turkey. Introductory Characteristics Form, “Athletic Identity Measurement Scale” (AIMS) and “Contentment with Life Assessment Scale (CLAS)” were used to collect data. The data were tested using SPSS 25 statistical program. The research results showed sports high school students had an athlete identity and life satisfaction above medium level. Students' athletic identities showed a statistically significant difference according to gender, age, affiliation to a club, years of practicing and weekly training frequency. It has been determined that students' life satisfaction differs significantly according to gender, age and weekly training frequency. It was concluded that there is a moderately positive (r=0.42) relationship between athlete identity and life satisfaction. Another important result is athlete identity is 17% effective in predicting life satisfaction.